The logical closure limit of superconductivity descriptions - Bousnane, Z.; Merabtine, N.; Benslama, M.; Boussaad, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The quantum description of macroscopic behaviour seems requiring the existence of limits imposed by the consideration hold on the logical closure of the theory, according to this, the J.A. Wheeler black box [1] will act under a coherence length of second order. The use of mathematical beings translating the phases transitions in nature are displayed in one-way, the reversibility parameter associated to the black box is severely limited according to the way we disturb the constants and the functions used to describe a given phenomenon. The combinatory formulation of matter is always accompanied by the length scales orientation phenomenon that must be seen as a measurement process of second order. The non-reproducibility of experiments will be dealing with the non-account of the amplitude of length scales interactions, this amplitude manages the combinatory of macroscopic levels between an observer and observed. Some introduced concepts as an entropic potential, the breaking of equivalence are making the emergence of picture of superconductivity as reproducible phenomenon according to the “intrinsic states reproducibility” with number estimated on universal constants expressions limited by the difference between cooled and cooling.